Leadership team coaching developing collective transformational leadership - Hawkins, Peter 1950- (Kogan Page, 2014)
Organizations are most effective when the teams responsible for the organization's success are performing to the best of their abilities. When the relationships within the team work well and all members of the team have a clear focus, the team has a significant impact on achieving goals and delivering results. Leadership Team Coaching is designed for people who have the responsibility to encourage and develop a team. It provides a thorough understanding of the role and importance of the team to organizational objectives and provides practical tools and techniques to facilitate effective team performance. Offering a practical road map with numerous examples, Peter Hawkins brings together the latest research to illustrate how to develop people from disparate groups into a high performing team to transform a business.The second edition of Leadership Team Coaching is completely updated and addresses latest developments in the world of leadership teams and team coaching. It takes an in-depth look at the area of coaching the board and includes new international case studies as well as new chapters on how to select the players for a high performing team and on how CEOs can develop effective teams with shared leadership.